Emotional maturity of early age marriage's woman - Farahdiba Thahura (INSPIRA: Indonesian Journal of Psychological Research, 2020)
Marriage is quite interesting to talk about more and more at this time because at this time many problems arise related to marriage because marriage is a complicated and complex thing. There are many things to be prepared for before someone decides to enter the marriage level, especially for a wife. The purpose of this study is to assess the extent of the role of emotional maturity of young wives in creating harmony in the family. Respondents in this study were women, aged 18-20 years in Aceh, marriage period of 0-3 years. The number of respondents is 2 people using qualitative research methods. The method of data collection in this study is by observation and interview using tape recorder tools and observation sheets. These internal and external factors affect whether or not the respondent is mature emotionally. This emotional immaturity is a reaction seen in every respondent. The maturity of respondents is different from each other. The respondents were aware of the impact on marriage at a young age but did not make the respondents dissolve in any conflicts that occurred due to immature emotions of the respondent, but rather made efforts to be able to control and overcome all conditions faced wisely and try to make positive efforts to foster family harmony.